Enhancing teacher-student relationship quality: A narrative review of school-based interventions. (November 2022) - Poling, Daniel V.; Van Loan, Christopher L.; Garwood, Justin D.; Zhang, Shuai; Riddle, David
Abstract: There is a large body of cross-sectional and longitudinal research that demonstrates the link between high-quality teacher-student relationships and numerous beneficial student outcomes such as reduced problem behavior, increased academic achievement, enhanced school engagement, and improved social standing among peers. Much less is known, however, about specific interventions that target teacher-student relationship quality. This article provides a comprehensive and integrative review of the literature on school-based interventions that included an outcome measure of teacher-student relationship quality. Our synthesis of 24 studies revealed four approaches targeting teacher-student relationship quality by (a) increasing closeness; (b) decreasing conflict; (c) promoting social-emotional learning; and (d) emphasizing relationship-driven classroom management. For each approach we describe the relationship building mechanisms, intervention components, effects, and conclusions. A final discussion includes common elements across intervention approaches, limitations and suggestions for future research, and implications for teacher training. Highlights: A literature review of school-based interventions that included an outcome variable of teacher-student relationship quality. A synthesis of 24 studies resulted in a conceptual framework of 4 unique yet interrelated relationship building approaches. Most studies included children in elementary school and only measured relationship quality based on teacher report data.